GAMBARAN HASIL PEMERIKSAAN KADAR HBA1C PADA PENDERITA DIABETES MELLITUS DI LABORATORIUM RUMAH SAKIT UMUM SURYA HUSADHA TAHUN 2013 - Airin Que; I Wayan Putu Sutirta Yasa; A.A. Wiradewi Lestari (E-Jurnal Medika Udayana, 2015)
THE HBA1C RESULT TEST OF PATIENTS WITH DIABETES MELLITUS IN THE LABORATORY OF SURYA HUSADHA HOSPITAL 2013Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia. In 2010, an estimated 285 million people suffer from diabetes worldwide and in 2030 an estimated 438 million people will suffer from diabetes worldwide. Effect caused by hyperglycemia affect the vascular system and long-term health, it takes the diagnosis and management of diabetes mellitus quickly and accurately. The diagnosis of diabetes can be enforced through a lot of things, one of which is a measurement of HbA1C (Glycated Hemoglobin atau Glycosylated Hemoglobin) levels. On examination of HbA1c does not require patients to fast, the results were not influenced by short-term lifestyle of the patient, because the patient's HbA1C describe long-term (2-3 months) blood sugar and blood sugar control patients. Indonesian Society of Endocrinology (PERKENI) in 2006 has categorized the results of laboratory tests HbA1C levels into 3 variables, good control (HbA1c levels <6.5%), moderate control (HbA1c levels of 6.5% - 8%), and poor control (HbA1c levels ? 8%). This study aims to describe the results of HbA1C levels in people with diabetes mellitus in the Laboratory of Surya Husadha Hospital during the year 2013. This study used cross sectional design, non experimental data obtained retrospectively from Surya Husadha Hospital Laboratory. The sample was all the result of HbA1C level among patients who were tested in the Surya Husadha Hospital Laboratory in 2013 with total 173 people. The result of this study was from 173 people who done the HbA1C level test in the Surya Husdha Hospital Laboratory in 2013, the results HbA1C levels of disease control, showed that good control was 64 people (36%), moderate controls was 46 people (25.8%) and poor control was 68 people (38.2%). Characteristics of patients according to gender, the male gender was 110 people (61.8%) and female gender was 68 persons (38.2%).